Body mass index and insulin use as identifiers of high‐cost patients with type 2 diabetes: A retrospective analysis of electronic health records linked to insurance claims data. Issue 6 (27th March 2019) - Johnston, Stephen S.; Ammann, Eric M.; Kashyap, Sangeetha R.; Stokes, Andrew; Hsiao, Carine Chia‐Wen; Daskiran, Mehmet; Scamuffa, Robin
Abstract : Aims: To study the association of body mass index (BMI) and insulin use with type 2 diabetes‐related healthcare expenditures (T2D‐HE). Materials and methods: Retrospective study using de‐identified electronic health records linked to insurance claims data. Study included a prevalence‐based sample of overweight or obese patients with antihyperglycaemic‐treated T2D. Patients had ≥1 A1c measurement in 2014 (last observed = index A1c ), ≥1 BMI measurement within ±90 days of index (average BMI = baseline BMI ), and continuous enrolment for 180 days before ( baseline ) through 395 days after index (day 30‐395 = follow‐up ). BMI was categorized as: 25 to 29.9 kg/m 2 = overweight; 30 to 34.9 kg/m 2 = obese class I (OCI); 35 to 39.9 kg/m 2 = OCII; ≥40 kg/m 2 = OCIII. Multivariable regressions were used to examine one‐year follow‐up T2D‐HE as a function of BMI, insulin use, an interaction term between BMI and insulin use, and patient demographics. Results: Study included 13 026 patients (mean age = 63.6 years; 48.1% female; 29.5% overweight, 31.6% OCI, 20.3% OCII, 18.6% OCIII; 25.3% insulin users). Baseline insulin use rates monotonically ranged from 19.7% in overweight patients to 33.0% in OCIII patients ( P < 0.001). Together, BMI and insulin use were jointly associated with one‐year follow‐up T2D‐HE, which monotonically ranged from $5842 in overweight patients with no insulin to $17 700 OCIII insulin users, P < 0.001. Within each BMI category, insulin users' one‐year T2D‐HE was at least double that of non‐users. Additional analyses of all‐cause healthcare expenditures yielded consistent results. Conclusions: BMI and insulin use represent simple stratifiers for identifying high‐cost patients. OCIII insulin users incurred the greatest annual healthcare expenditures; these patients may be an ideal group for targeted interventions.